Evaluasi Program Ekstrakurikuler Baca Tulis Al-Qur'an di Madrasah Tsanawiyah Negeri Klaten - Rahmawati, Ayu Putri; Khuriyah, Khuriyah; Wahyuningsih, Retno (Center of Language and Cultural Studies, 2021)
The research aims to evaluate the process of implementing Qur’an reading and writing extracurricular programs and know the student's ability of Qur’an reading and writing in Madrasah Tsanawiyah Negeri 3 Klaten. The research used a mixed-method with a CIPP evaluation model assigning 92 students as a sample. Data were collected using interviews, observation, questionnaires, documents, and tests. Results show that overall the evaluation process was good because it was in accordance with what is expected by the school. The implementation of Qur’an reading and writing extracurricular was appropriate with RPP Qur’an Hadist. In its implementation, 84,8% of students achieved good category. The evaluation product, an extracurricular program in Qur’an reading and writing achieved good results, indicating 57,61% good in reading; 18,48% very good. It means that more than 75% of students that joined extracurricular were successful in reading and writing Al-Qur’an well. The students are able to recite Al-qur’an verses fluently, recite some tajwid well and right, and can read Al-qur’an clearly and tartil.